2019
DOI: 10.1002/etc.4599
|View full text |Cite
|
Sign up to set email alerts
|

A Toxicokinetic Framework and Analysis Tool for Interpreting Organisation for Economic Co-operation and Development Guideline 305 Dietary Bioaccumulation Tests

Abstract: The Organisation for Economic Co-operation and Development guideline 305 for bioaccumulation testing in fish includes the option to conduct a dietary test for assessing a chemical's bioaccumulation behavior. However, the onecompartment toxicokinetic model that is used in the guidelines to analyze the results from dietary bioaccumulation tests is not consistent with the current state of the science, experimental practices, and information needs for bioaccumulation and risk assessment. The present study presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 26 publications
1
39
1
Order By: Relevance
“…Moreover, the eye is extremely vascularized organ, so any long-term contact may allow molecules to enter systemic circulation. The eye itself is sensitive and prone to damage from chemical exposure [48]. We found that NZW rabbits instilled with rEP showed irritation within 1 h that lasted up to 72 h. Notably rEP treatment did not cause any long-term corneal opacity, conjunctival redness, or abnormality of the iris, and therefore, it can be considered as safe for eyes [49].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, the eye is extremely vascularized organ, so any long-term contact may allow molecules to enter systemic circulation. The eye itself is sensitive and prone to damage from chemical exposure [48]. We found that NZW rabbits instilled with rEP showed irritation within 1 h that lasted up to 72 h. Notably rEP treatment did not cause any long-term corneal opacity, conjunctival redness, or abnormality of the iris, and therefore, it can be considered as safe for eyes [49].…”
Section: Discussionmentioning
confidence: 80%
“…The first component was simply plotting the reported BMF L and BMF 5% versus the reported lipid content of the diet. The second component involved analyzing the original experimental concentration–time data in Hashizume et al (2018) of the 2 paired tests using the ADME‐B Calculator (Gobas et al 2019). This was first done for the experiments conducted with the lower–lipid content diet.…”
Section: Methodsmentioning
confidence: 99%
“…This dietary biomagnification model has been incorporated in food web bioaccumulation models and corroborated with thousands of field bioaccumulation metrics (e.g., Arnot and Gobas 2004). The dietary biomagnification model was updated to include intestinal biotransformation and proposed as a toxicokinetic framework for interpreting the results of OECD 305 dietary bioaccumulation tests (Lo et al 2015, 2016; Gobas et al 2019). When updated to include biotransformation in the intestinal tract, the model can be expressed in terms of 2 mass balance equations (i.e., one for the intestinal tract and one for the body of the fish), which in fugacity format, to illustrate the magnification process, are VG×ZG×dfnormalGdt=DD×fD+DBG×fB(DGB+DGE+DGM)×fG VB×ZB×dfnormalBdt=DGB×fG(DBG+DnormalB2+DBM+DBQ)×fBwhere f B is fugacity in the body of the fish (pascals), f D is fugacity in the diet (pascals), f G is fugacity in the digesta (pascals), V B is the volume of the body of the fish (cubic meters), V G is the volume of the digesta (cubic meters), Z B is the fugacity capacity of the body of the fish (moles per cubic meter per pascal), Z G is the fugacity capacity of the digesta (moles per cubic meter per pascal), D D is the transport parameter for food ingestion (moles per pascal per day), D GE is the transport parameter for the egestion of digesta from the gastrointestinal tract (moles per pascal per day), D GM is the transport parameter for gastrointestinal biotransformation (moles per pascal per day), D BG is the transport parameter for chemical transfer from the body of the fish to the digesta (moles per pascal per day), D GB is the transport parameter for chemical transfer from the digesta to the body of the fish (moles per pascal per day), D B2 is the transport parameter for chemical transfer from the body of the fish to the water via the respiratory surface (e.g.,...…”
Section: Theorymentioning
confidence: 99%
“…Data relevance and reliability need to be considered to establish confidence in a chemical assessment. A weight of evidence (WoE) approach (Weed 2005 ; Hope and Clarkson 2014 ; OECD 2019 ; Suter et al 2020 ) can inform B assessment decision‐making given the various metrics and criteria and inherent variability and uncertainty in the underlying data (Barber 2003 ; Burkhard 2003 , 2008; Arnot and Gobas 2006 ; Parkerton et al 2008 ; Crookes and Brooke 2010 ; Borgå et al 2012 ; Burkhard et al 2012 , 2013 ; Arnot and Quinn 2015 ; Gobas et al 2020; Wassenaar et al 2020 ). Indeed, a WoE approach for B assessment is recommended under Annex XIII of the Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) legislation in the European Union (EC 2011 ; Moermond et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%